Evaluation of Type 322 Un-Signalized Intersection Performance - Radjawane, Louise Elizabeth; Lao, Virginia Claudia (International Journal of Science, Technology & Management, 2023)
Currently the world is trying to improve air quality which has an impact on climate change. Including Indonesia contributing to various international forums that discuss greenhouse gas emission reduction programs, including in the transportation sector. The Batua Raya-Toddopuli-Borong Raya intersection is an alternative intersection for travelers from Makassar City to Sungguminasa City or Maros City, and vice versa. The aim of this research is to obtain the delay and the relationship between the delay and the emission load at the un-signalized intersection of the Batua Raya-Toddopuli-Borong Raya road, Makassar, SIDRA INTERSECTION 8 Software is used to calculate the value of the delay and emission load. Delays that occur on weekdays are higher than holidays, seen on Monday morning at peak hours 17.00-18.00 there is a very high intersection delay of an average of 3888.52 seconds. The relationship between traffic delays and NOx emissions, which has an effect of 84.32%, each second addition of the delay value can increase HC emissions by 0.0000005 kg/hour. The relationship between traffic delays and CO emissions, which has an effect of 95.56%. The relationship between traffic delays and HC emissions, which has an effect of 93.76%. The relationship between traffic delays and CO2 emissions, which has an effect of 93.64%. The addition of delay time at the intersection increases the emission value and reduces the quality of the intersection level of service.